2020
DOI: 10.3390/ijms21207779
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Based Pharmacophore Modeling, Molecular Docking, and Molecular Dynamic Studies of Dual Tyrosine Kinase Inhibitor of EGFR and VEGFR2

Abstract: Epidermal growth factor receptor (EGFR) and vascular endothelial growth factor receptor 2 (VEGFR2) play an important role in cancer growth. Both of them have close relationships. Expression of EGFR will induce an angiogenic factor (VEGF) release for binding with VEGFR2. However, the existence of VEGF up-regulation independent of EGFR leads to cancer cell resistance to anti-EGFR. Therefore, a therapeutic approach targeting EGFR and VEGFR2 simultaneously may improve the outcome of cancer treatment. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…As shown in Table 4, PAP-3 displayed forming hydrogen bonds with Lys721 and Asp831. These hydrogen bonds have been reported previously by (Sangande et al, 2020). Particularly, the residue Asp831 is part of the DFG (Asp-Phe-Gly) motif which plays a key role in ATP binding and is relevant for the increased inhibitory activity of the receptors (Peng et al, 2013).…”
Section: Protein Kinasessupporting
confidence: 77%
“…As shown in Table 4, PAP-3 displayed forming hydrogen bonds with Lys721 and Asp831. These hydrogen bonds have been reported previously by (Sangande et al, 2020). Particularly, the residue Asp831 is part of the DFG (Asp-Phe-Gly) motif which plays a key role in ATP binding and is relevant for the increased inhibitory activity of the receptors (Peng et al, 2013).…”
Section: Protein Kinasessupporting
confidence: 77%
“…Thienyl-based VEGFR-2 inhibitors have been published, such as chalcone derivatives with thienyl moieties, which showed considerable VEGFR-2 inhibitory activities as well as activities against HUVEC cells as an angiogenesis cell model [ 14 ]. Several works about new VEGFR-2 inhibitors were disclosed, which indicate the clinical potential and importance of this research field [ 39 , 40 , 41 ]. Compound 1c also inhibited the receptor tyrosine kinase c-Kit, which is a cell growth promoting factor and a relapse risk enhancer in hepatoma [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating pieces of evidence have confirmed that VEGFR2 is closely related to EGFR and is involved in the development of multiple types of tumors [74,75]. Thus, the combination of VEGFR2 inhibitors and EGFR inhibitors can be promising in antitumor treatment.…”
Section: Dual Vegfr2-egfr Inhibitorsmentioning
confidence: 99%